Pengaruh Pijat Bayi Terhadap Perubahan Reflek Pada Bayi Dengan Down Syndrome di Ruang NICU : Case Report - Khoirunnisa Nurrahmah; Ferika Indarwati; Winarni Winarni (Protein : Jurnal Ilmu Keperawatan dan Kebidanan., 2024)
Down syndrome (DS) is a physical disorder caused by an excess of the third chromosome in the 21st pair of chromosomes which causes the number of chromosomes to become 47. One of the symptoms of Down syndrome is muscle weakness which can affect the baby's reflexes. To assess the effect of baby massage intervention on the reflex development of babies with Down syndrome in the NICU. The method used in this research is a case study with baby massage intervention for Down syndrome patients in the NICU. The intervention was carried out for 3 days. Baby massage intervention is carried out once a day with a duration of 10 -15 minutes. The results of this case study show that after baby massage there were changes in the palmar grasp reflex and Babinski reflex. Baby massage can improve babies’ reflexes particularly palmar and Babinski reflexes on babies with Down syndrome in the NICU.